SARS-CoV-2 Spike Protein Extrapolation for COVID Diagnosis and Vaccine Development - Malik, Yashpal S.; Kumar, Prashant; Ansari, Mohd Ikram; Hemida, Maged G.; El Zowalaty, Mohamed E.; Abdel-Moneim, Ahmed S.; Ganesh, Balasubramanian; Salajegheh, Sina; Natesan, Senthilkumar; Sircar, Shubhankar; Safdar, Muhammad; Vinodhkumar, O. R.; et al. (Frontiers in Molecular Biosciences, 2021)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) led to coronavirus disease 2019 (COVID-19) pandemic affecting nearly 71.2 million humans in more than 191 countries, with more than 1.6 million mortalities as of 12 December, 2020. The spike glycoprotein (S-protein), anchored onto the virus envelope, is the trimer of S-protein comprised of S1 and S2 domains which interacts with host cell receptors and facilitates virus-cell membrane fusion. The S1 domain comprises of a receptor binding domain (RBD) possessing an N-terminal domain and two subdomains (SD1 and SD2). Certain regions of S-protein of SARS-CoV-2 such as S2 domain and fragment of the RBD remain conserved despite the high selection pressure. These conserved regions of the S-protein are extrapolated as the potential target for developing molecular diagnostic techniques. Further, the S-protein acts as an antigenic target for different serological assay platforms for the diagnosis of COVID-19. Virus-specific IgM and IgG antibodies can be used to detect viral proteins in ELISA and lateral flow immunoassays. The S-protein of SARS-CoV-2 has very high sequence similarity to SARS-CoV-1, and the monoclonal antibodies (mAbs) against SARS-CoV-1 cross-react with S-protein of SARS-CoV-2 and neutralize its activity. Furthermore, in vitro studies have demonstrated that polyclonal antibodies targeted against the RBD of S-protein of SARS-CoV-1 can neutralize SARS-CoV-2 thus inhibiting its infectivity in permissive cell lines. Research on coronaviral S-proteins paves the way for the development of vaccines that may prevent SARS-CoV-2 infection and alleviate the current global coronavirus pandemic. However, specific neutralizing mAbs against SARS-CoV-2 are in clinical development. Therefore, neutralizing antibodies targeting SARS-CoV-2 S-protein are promising specific antiviral therapeutics for pre-and post-exposure prophylaxis and treatment of SARS-CoV-2 infection. We hereby review the approaches taken by researchers across the world to use spike gene and S-glycoprotein for the development of effective diagnostics, vaccines and therapeutics against SARA-CoV-2 infection the COVID-19 pandemic.